Building Tolerance through Hindu Religious Textbooks: Teaching Tolerance Values to Elementary School Students through Stories and Illustrations - Busro, Busro; Gateri, Ni Wayan (Jayapangus Press, 2023)
Religious education in Indonesia has an important role in shaping students' character and tolerance. However, there are still challenges in integrating tolerance values in religious textbooks. The purpose of this study is to analyze the elements of tolerance in Hinduism textbooks for elementary school students. This research used a content analysis approach to analyze the elements of tolerance in the stories and illustration pictures of Hindu religious textbooks for elementary school students. The results showed that the elements of tolerance in the textbooks could be grouped into an appreciation for differences, understanding of diversity, cooperation and brotherhood, and justice. These findings indicate that Hindu religious textbooks can be an effective means to promote values of tolerance among elementary school students. The scientific contribution of this study is that content analysis can be used to identify the elements of tolerance in Hindu religious textbooks for elementary school. The significance of this research lies in its implications for educators and curriculum developers. By highlighting the elements of tolerance, this study underscores the importance of incorporating these values into religious education curricula. It emphasizes the need for educators and textbook authors to pay attention to and reinforce tolerance elements in the content and design of religious textbooks. In doing so, religious education can effectively contribute to the development of diverse and understanding communities among elementary school students in Indonesia.